Differential Expression of HOX Genes in Mesenchymal Stem Cells from Osteoarthritic Patients Is Independent of Their Promoter Methylation - Arkaitz Mucientes; Eva Herranz; Enrique Moro; Cristina Lajas; Gloria Candelas; Benjamín Fernández-Gutiérrez; José Ramón Lamas (Cells, 2018)
Skeletogenesis, remodeling, and maintenance in adult tissues are regulated by sequential activation of genes coding for specific transcription factors. The conserved Homeobox genes (HOX, in humans) are involved in several skeletal pathologies. Osteoarthritis (OA) is characterized by homeostatic alterations of cartilage and bone synthesis, resulting in cartilage destruction and increased bone formation. We postulate that alterations in HOX expression in Mesenchymal Stem cells (MSCs) are likely one of the causes explaining the homeostatic alterations in OA and that this altered expression could be the result of epigenetic regulation. The expression of HOX genes in osteoarthritic-derived MSCs was screened using PCR arrays. Epigenetic regulation of HOX was analyzed measuring the degree of DNA methylation in their promoters. We demonstrate the downregulated expression of HOXA9 and HOXC8 in OA-MSCs. However, their expression does not correlate with promoter methylation status, suggesting that other epigenetic mechanisms could be implicated in the regulation of HOX expression. Studies on the role of these genes under active differentiation conditions need to be addressed for a better knowledge of the mechanisms regulating the expression of HOX, to allow a better understanding of OA pathology and to define possible biomarkers for therapeutic treatment.